The Effectiveness of Using Pre-Screening Questionnaires to Improve Mother's Knowledge and Skills in Implementing Early Detection of Early Childhood Development - Ningsih Jaya; Ambo Dalle; Bahtiar Bahtiar (Journal of Global Pharma Technology, 2020)
Early childhood development can be detected through developmental pre-screening, with the aim of detecting early developmental disorders. The research objective was to analyze the effectiveness of the use of pre-screening questionnaires to improve the knowledge and skills of mothers in detecting early childhood development. The design of this study was a pre test - post test, involving 60 mothers of children under five. Observations were made before and after the intervention. Data were analyzed using the Wilcoxon test. The results showed that there was an increase in maternal knowledge and skills after being given the intervention. Thus, it can be concluded that the use of developmental pre-screening questionnaires is effective in increasing the knowledge and skills of mothers under five in early detection of child development. Keywords: Child Development, Child Development Pre-Screening Questionnaire, Knowledge, Skills